Erythrocyte plasma membrane redox system in human aging - Rizvi, Syed Ibrahim; Jha, Rashmi; Maurya, Pawan Kumar (Rejuvenation research, 2006)
Eukaryotic cells display a plasma membrane redox system (PMRS) that transfers electrons from intracellular substrates to extracellular electron acceptors. The physiologic importance of PMRS is still not fully understood. The authors have carried out studies to determine the activity of PMRS in human erythrocytes as a function of age and correlate the activity with total plasma antioxidant capacity in an effort to understand the role of PMRS in human aging. The study was carried out on 80 normal healthy subjects of both genders between the ages of 18 and 85 years. The activity of erythrocyte PMRS was estimated by following the reduction of ferricyanide. The total antioxidant capacity of the plasma was estimated in terms of Ferric Reducing Ability of Plasma (FRAP) values. A significant (p < 0.0001) positive correlation (r = 0.7797) is observed between PMRS activity of erythrocytes and human age. There is an age-dependent decrease in total plasma antioxidant capacity measured in terms of FRAP values. A highly significant correlation is observed between PMRS activity and plasma FRAP values. The authors hypothesize that the increased PMRS in erythrocytes during aging may be a protective mechanism of the system for efficient extracellular DHA reduction and ascorbate recycling under condition of increased oxidative stress.